Pengaruh Tahanan Jenis Tanah Terhadap Sistem Pentanahan Menggunakan Elektroda Batang Dilokasi Gedung Teknik Elektro Unimal - Hardi, Gery U.; Taufiq, Taufiq; Raihan Putri; Nasution, Fakhruddin A (Yayasan Literasi Sains Indonesia, 2023)
Providing a return line for short-circuit currents or fault currents to a low-resistance ground, grounding system is useful for achieving a uniform potential voltage over a given area of buildings and equipment. Because a large voltage difference can occur if a fault current is forced to ground against a high resistance. Placement of the electrode to be planted is one of the elements to obtain a low grounding resistance value. Grounding resistance measurements, which will serve as a guide for the grounding system design process, are required during the planning stage for certain types of grounding systems. The problem is how the grounding resistance is affected by the buried depth of the rod conductor and the soil type resistance. Therefore, it is very important to conduct research and testing to determine the extent to which these parameters influence. The experimental results of measuring resistance on dry and wet soils are on dry soil 30 cm obtained 98.48 Ω, 60 cm obtained 37.07 Ω, 90 cm obtained 20.52 Ω, 120 cm obtained 19.77 Ω, and for wet soil at a depth of 30 cm obtained 43.34 Ω, 60 cm obtained 22.21 Ω, 90 cm obtained 15.43 Ω, 120 cm obtained 11.66 Ω. So to get the 5Ω value we make an estimate by adding a depth of 56.603 cm for wet soil and 38.58 cm for dry soil, then the length of the electrode needed is 176.603 cm for wet soil and 158.58 cm for dry soil.